2014
DOI: 10.1111/jam.12488
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostics on the toxigenic potential of F usarium spp. plant pathogens

Abstract: AimsWe propose and test an efficient and rapid protocol for the detection of toxigenic Fusarium isolates producing three main types of Fusarium-associated mycotoxins (fumonisins, trichothecenes and zearelanone).Methods and ResultsThe novel approach utilizes partially multiplexed markers based on genes essential for mycotoxin biosynthesis (fumonisin—fum6, fum8; trichothecenes—tri5, tri6; zearalenone, zea2) in Fusarium spp. The protocol has been verified by screening a collection of 96 isolates representing dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The chemotype and species determination as well as procedures used for their cultivation, identification and storage were described previously by Dawidziuk et al (2014). All investigated fungal isolates originated from culture collections of the Functional Evolution of Biological Systems Team (Institute of Plant Genetics, Polish Academy of Sciences, Poznan, Poland).…”
Section: Samples Collection and Identificationmentioning
confidence: 99%
“…The chemotype and species determination as well as procedures used for their cultivation, identification and storage were described previously by Dawidziuk et al (2014). All investigated fungal isolates originated from culture collections of the Functional Evolution of Biological Systems Team (Institute of Plant Genetics, Polish Academy of Sciences, Poznan, Poland).…”
Section: Samples Collection and Identificationmentioning
confidence: 99%
“…But any PCR products were amplified by the primer sets, which taken into consider the toxigenic capacity of the pathogens in the maize samples. However, when the standard PCR was performed against the tissues of infected samples, the positive results only came from the infected wheat kernel, rather than the wheat chaff . Furthermore, Lezar and Barros reported an oligonucleotide microarray to identify potential mycotoxigenic fungi, in which the oligonucleotide probes were designed by EF‐1a or genes involved in the mycotoxin synthetic pathways.…”
Section: Polymerase Chain Reaction Diagnosis For Fusarium Species Assmentioning
confidence: 99%
“…The results clearly revealed a sensitive and specific detection of the toxigenic Fusarium isolates with the sensitivity (100%) and specificity (95%) for the trichothecenes-producing fungi, the sensitivity (100%) and specificity (100%) for the zearalenone-producing fungi, as well as the sensitivity (94%) and specificity (88%) for the fumonisins-producing fungi. 18 Nielsen et al reported a quantitative real-time PCR assay based on polymorphism of Tri12 gene in trichothecene biosynthesis cluster to identify and quantify the genotypes based on the trichothecene composition, i.e. 3-acetyl-deoxynivalenol (3ADON), 15-acetyl-deoxynivalenol (15ADON) and nivalenol (NIV), in the Fusarium species in Danish cereals.…”
Section: Advanced Assays Used For the Detection Of Mycotoxin-producinmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Molecular techniques based on DNA analysis are being widely used to identify and discriminate among isolates within a species and to develop rapid, sensitive, and accurate detection methods (Mule et al, 2005;Nicolaisen et al, 2005). Furthermore specific PCR helps in accurate discrimination of fumonisin (FB) producing and nonproducing Fusarium isolates occurring on cereal grain (Dawidziuk et al, 2014). Researchers use genes from the FUM cluster as a good additional marker for phylogenetic and taxonomic studies of the fumonisin-producing Fusarium species (Baird et al 2008;Stepien et al 2011).…”
Section: Introductionmentioning
confidence: 99%